Search for light resonances decaying to boosted quark pairs and produced in association with a photon or a jet in proton–proton collisions at √s = 13 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2018)
This Letter presents a search for new light resonances decaying to pairs of quarks and produced in association with a high-pT photon or jet. The dataset consists of proton–proton collisions with an integrated luminosity of 36.1 fb−1 at a centre-of-mass energy of √s = 13 TeV recorded by the ATLAS detector at the Large Hadron Collider. Resonance candidates are identified as massive large-radius jets with substructure consistent with a particle decaying into a quark pair. The mass spectrum of the candidates is examined for local excesses above background. No evidence of a new resonance is observed in the data, which are used to exclude the production of a lepto-phobic axial-vector Z boson.